(3CbQH GdCOdI aj ESJNQGL GdCgdIs - (3TeS GdOjf Hf YHO Gddg Hf aJM GdaQZdj GdSHQHGFj,J (B1210 (3g` s
(3ChdgG (B:s
(3jGef LYd GdTeS VjGA , hGdbeQ fhQkG CeG HYO , ajbhd TeS GdOjf deG cGf aef GdJbhje ef CMSf Gdafhf JYdbJ Hg gee GdCaGVd hcGf ef CLd eG Ufa ai gPG Gdaf HYO GdCRjGL GdeWhdI s
(3BNQgG (B:s
(3LOhd ajg CSeGA GdHdGO (B: (3CfbQI SeQbfO GdTGS , aQZGfI bfG s
(3HgG fXGe GdJYbjHIs
(3eYXegG LOGhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B307s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs